MINE SLOPE DESIGN SIMULATIONS USING SLIDE 6.0 SOFTWARE OF POST-MINING SLOPE STABILITY - Rahma Norfaeda; Tommy Maulidyanto; Kartini (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Post-mining slopes are susceptible to landslides due to factors such as slope geometry, rock structure, physical and mechanical properties of rocks, and groundwater content. Monitoring of these slopes is essential to prevent broader environmental issues. This research aims to determine the stability of former mining slopes using soil samples from the Mataraman District, Banjar Regency. The technical analysis method focuses on the physical and mechanical properties of soil, supplemented with mine slope design simulations using Slide 6,0 software to ascertain the safety factors from various slope angles. Safety factor analysis considers the smallest cohesion and bulk density values to represent the material strength of the slope. Findings indicate that the post-mining slopes would remain stable and safe provided no additional destabilizing factors are introduced. The slopes maintain a safety factor greater than 2, implying stability even with a steepness up to 70°. Keywords: mining slope stability, safety factor